PENGARUH TINGKAT PENGETAHUAN OBAT DAN PENYAKIT HIPERTENSI TERHADAP KEPATUHAN PENGAMBILAN OBAT PENDERITA HIPERTENSI DI PUSKESMAS ROWOREJO KABUPATEN PESAWARAN LAMPUNG - Dwi Efayanti; Subur Widodo; Ade Kristanto (JFL : Jurnal Farmasi Lampung, 2020)
ABSTRACT Hypertension is a disease that contributes to death by 29.8%, factors that cause an increase in the prevalence of hypertension include patient compliance, compliance itself is influenced by one's behavior factors, one of which is knowledge. This study aims to look at the effect of the level of knowledge on the compliance of taking drugs with hypertension in Roworejo Public Health Center, Pesawaran Regency, Lampung. This research is a descriptive analysis research, conducted by giving a questionnaire that has been tested for validity and reliability and has obtained ethical permission from the ethics committee of Malahayati University, Bandar Lampung with No.485 / EC / Kep-UNMAL / VII / 2019. The level of compliance with drug taking can be seen from the recap of prescriptions for hypertension in April-June 2019. The category of adherence level uses the formula MPR (Medication Possession Ratio) which is <80% categorized as non-compliant and> 80% categorized as compliant. The data is then analyzed using linear regression, if the significant value <0.05 means that there is an influence between the variable X on the Y variable, if the significant value> 0.05 means that there is no influence between the variable X on the Y variable. The results showed that the most hypertensive patients aged> 60 years 81%, female sex 59%. The level of knowledge of the respondents mostly had medium knowledge 98% and high knowledge 2%. The level of compliance with respondent's drug taking was only 3% of respondents who were compliant and 97% of respondents were not compliant From the results of linear regression analysis in this study showed that the value of Significant value 0.000> 0.05, which can be concluded that there is an influence between the variable level of knowledge of the level of compliance with drug taking. Keywords: Hypertension, Compliance with drug uptake, Knowledge, MPR, Roworejo.